2011
DOI: 10.1258/ar.2011.100360
|View full text |Cite
|
Sign up to set email alerts
|

Unenhanced fat fraction ratios obtained by MR and enhanced T2* values with liver-specific MR contrast agents for diagnosis of non-alcoholic steatohepatitis in rats

Abstract: Pre-enhancement FFR, T2* value measurement and reduction rate of T2* value on SPIO-enhanced MRI may help estimate the progress of liver fat deposition and fibrosis in NASH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Hepatic T 2 * variations among different segments have been shown to be low in healthy subjects, ranging between 19.3 and 29.9 ms [42], which is in accordance with our observations. Similar results were obtained in an animal study where the T 2 * of liver parenchyma of rats decreased from 31.4 ms for the control group (0.9% HFF) to 19.1 ms for rats fed by a four week choline-deficient diet (26.0% HFF) [43]. A clinical study on patients with non-alcoholic fatty liver disease (NAFLD) reported significant decreases of T 2 relaxation times of water with increasing fat fractions [19].…”
Section: Discussionsupporting
confidence: 87%
“…Hepatic T 2 * variations among different segments have been shown to be low in healthy subjects, ranging between 19.3 and 29.9 ms [42], which is in accordance with our observations. Similar results were obtained in an animal study where the T 2 * of liver parenchyma of rats decreased from 31.4 ms for the control group (0.9% HFF) to 19.1 ms for rats fed by a four week choline-deficient diet (26.0% HFF) [43]. A clinical study on patients with non-alcoholic fatty liver disease (NAFLD) reported significant decreases of T 2 relaxation times of water with increasing fat fractions [19].…”
Section: Discussionsupporting
confidence: 87%
“…This explains the rather good hepatic enhancement (gadoxetic acid uptake) measured in our patients, ranging from 46% to 130%, and also why it was not linked with the phenomenon of HP-negative lesions [24]. Furthermore, bilirubin is a known competitor of gadoxetic acid at the membrane transporter of hepatocytes and also a marker of impaired liver function [25,26]. Therefore, one exclusion criterion in this study was a total bilirubin >2 mg/dL.…”
Section: Discussionmentioning
confidence: 67%
“…The quantitative T2* relaxometry technique was reported to be able to differentiate the progression of NASH in the rat model through a dynamic MRI sequence with Resovist (Table 1, entry 8). 24 Significant changes of the MR T2* rate over the time period from 3 to 10 min post-injection were observed as the NASH model progressed from 4, 7, to 10 weeks, possibly related to the increased dysfunctional level of Kupffer cells. Meanwhile, the development of more biocompatible and stable SPIONs for chronic liver diseases has been reported through modification of coating materials such as poly(vinyl acetate-methylacrylic acid)/chitosan using a layer by layer technique, dextran, and citrate (Table 1, entries 9− 11).…”
Section: ■ Introductionmentioning
confidence: 88%
“…Pathology staining analysis suggested that SPIONs delivered through BMSC were mainly located in the periportal and injured regions, different from that of SPION alone as in the liver Kupffer cells. The quantitative T2* relaxometry technique was reported to be able to differentiate the progression of NASH in the rat model through a dynamic MRI sequence with Resovist (Table , entry 8) . Significant changes of the MR T2* rate over the time period from 3 to 10 min post-injection were observed as the NASH model progressed from 4, 7, to 10 weeks, possibly related to the increased dysfunctional level of Kupffer cells.…”
Section: Spions As An Effective Mri Contrast Agent For Chronic Liver ...mentioning
confidence: 99%